Pengetahuan Ibu Tentang Posyandu Dengan Cakupan Kunjungan (D/S) Balita (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background : Based on the Republic of Indonesia Ministry of Health in 2013 the coverage (D / S) oftoddlers in Indonesia amounted to 80.30%, in the Special Region of Yogyakarta in 2014 reached79.1% had not met the Ministry of Health Renstra target, the level of community participation in BantulRegency in weighing Posyandu (D / S) of 79.02% and still below 80%, the number of under-fivedeaths in Bantul Regency in 2014 was 131 toddlers, the highest number of under-five mortalityamong the five regencies in DIY, for D/S coverage which was still low in Bantul Regency below 80%namely Bantul 1 Health Center is 75.47%, in the Bantul I Health Center area the scope of weighing(D/S) is still low, namely in Trirenggo Village the D / S coverage in October 2015 was 75.95%.Objective: To find out the relationship between the knowledge of mothers about posyandu and thecoverage of visits (D / S) of toddlers at Posyandu Mekarsari, Trirenggo, Bantul, Yogyakarta.Method: This study was conducted at Mekarsari Trirenggo Bantul Posyandu in February, the studydesign used Bivariate Correlation with a cross sectional approach. The population of mothers whohave children aged 12-60 months who live in the Mekarsari Posyandu area is 65 respondents. Thesampling technique by means of total sampling. Analysis using Chi Square.Results: By using the Chi Square formula, the value of X2 calculated is equal to6,644 with an error rate of 5% (X2 count> X2 table) and p-value